SELF-EFFICACY DAN PENDIDIKAN (Kajian Teori Kognitif Sosial dan Implikasinya dalam Pendidikan Agama Islam) - Moh Toriqul Chaer (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2016)
Abstract: learning is a process of change in human personality, and the changes are showed in the form of an increase in the quality and quantity of behaviors such as increased skills, knowledge, attitudes, habits, understanding, skills, mindset, and other capabilities. One of the famous psychologist with the learning theory is Albert Bandura. Bandura is a psychology that greatly contribute to the formation of the child's behavior through learning in the tradition of behaviorists theories and analytical study. A very popular Bandura's theory is a theory of Social Learning, which emphasizes the cognitive components of mind, understanding, and evaluation. Self-Efficacy is one aspect of knowledge about self or self however knowwledge of the most influential in the lives of everyday maanusia. This is due to Self-Efficacy influences the individual owned participated in determining the action to be performed to achieve a goal of including an estimate of the various events that will be encountered. Self-Efficacy is one of the capabilities of the individual settings. The concept of Self-Efficacy was first propounded by Bandura in 1991. Self-Efficacy refers to the perception of the ability of individuals to organize and implement actions to display certain skills. This theory lies in three factors reciprocal determinism, personal factors, behavioral, and environmental influences, which have a positive effect to be implemented in education, in particular the Islamic education.Keywords; Self-Efficacy, Social Learning Theory, Islamic education